X-ray structure analysis of symmetrically substituted 1,1′-diformylruthenocene - Bertin Anzaldo; Pankaj Sharma; Francisco Lara Ochoa; Claudia P. Villamizar C.; René Gutiérrez Pérez (Acta Crystallographica Section E: Crystallographic Communications, 2018)
1,1′-Diformylruthenocene, [Ru(C6H5O)2], crystallizes in the orthorhombic system in the P212121 space group at room temperature. There are two crystallographically independent molecules in the asymmetric unit. The cyclopentadienyl rings have eclipsed configuration. The molecules self-assemble in a two-dimensional structure by C—H...O and C—H...π interactions with cisoid relative orientations of the two formyl groups. The crystal studied was refined as an inversion twin.